Rancang Bangun Alat Sintesis Serbuk Biji Pinang Menjadi Tinta Batik - Hilda Porawati; Sandi Yudha Barri Zaqy; Andika; Rizki Prastyo (Jurnal INOVATOR, 2023)
Batik is Indonesia's cultural heritage where each region has its own characteristic style and different batik motifs. Batik dyes can be obtained from synthetic dyes and natural dyes. In this research is the synthesis of betel nut powder with wax and paraffin into batik ink. The synthesis was carried out on a tool that had been made with the main components, namely a reservoir, a heating system, an automatic stirrer system and temperature readings using a bimetal thermometer. The results showed that the solvent and wax will melt at a temperature of 90oC to 110oC. The mixture of areca nut powder with wax and paraffin produces a dark brown color that can be used as a natural dye for batik